Look at me Playing? – The eSports importance on consumers emotions - Morais, A.; Oliveira, A.; Pinheiro, A. (Eurasian Conference on Frontiers of Computer Science and Information Technology (FCSIT 2022), 2022)
The world of video games is not only gaining a growing number of fans but is also getting more and more attention from the media and social networks. The eSports are electronic sports known as competitive video gaming and have already a large following all over the world, over the past few years, being a phenomenon of audiences. Alongside this growth, scientific interest in studying this topic has also been growing, as shown by the significant number of scientific papers that have been published on this subject. The research about the effects that eSports have on its players has different perspectives, such as positive or negative impacts. Thus, supported by what has been studied and documented in previous studies – according to the available research papers (indexed in journals or international conferences) –, it is important to understand what the importance of the eSports for its players and spectators is. This study enhances what has already been investigated about this topic. Starting with our research question ‘How do esports affect their consumers emotionally?’, a systematic review was conducted to resume and analyze the impacts that competitive video gaming has emotionally on eSports’ consumers. According to the defined inclusion criteria, 20 relevant published papers were selected through the electronic databases Google Scholar and Scopus, published between 2016 and 2022, and a deep analysis of the literature – a meta-analysis – was conducted. Iramuteq and MonkeyLearn software were used to determine and shape the main themes and concepts of emotional impacts, through textual analyses. This review draws insight into the effects that competitive video gaming has on the mental health of the players and suggests that future studies may focus on some interventions to deal with the negative impact that eSports has emotionally.